Percepção dos estudantes da 3ª série do ensino médio de uma escola pública do município de Alegre/ES sobre impactos ambientais - Pires, Marceli Gonçalves (2024)
A range of degrading events, such as floods, global warming, and heat waves, which have been affecting the environment and are frequently reported in various media, daily reflects concerns about the many forms of “environmental impacts”. This theme is indicated in the National Common Curricular Base (BNCC) to be addressed in subjects such as Biology, with the aim of fostering students’ understanding of the topic for the development of environmentally conscious citizens who recognize the importance of sustainability. Thus, the guiding question explored in this research arose: Does the subject of Biology contribute to the development of individuals by promoting, among 3rd-year students, a more critical perspective on anthropogenic events that affect the environment, particularly environmental impacts? This research aimed to analyze the perceptions of 3rd-year high school students from a school in the municipality of Alegre, Espírito Santo, on the theme of “environmental impacts”. The specific objectives were: a) to compare students’ perceptions of different types of environmental impacts before and after a practical activity in a non-formal educational setting; b) to correlate the content taught with the specific competencies of the BNCC. A participatory qualitative research approach was adopted, with direct and systematic observations of the perceptions of sixteen 3rd-year high school students from a school in Alegre/ES. Data collection instruments included conversation circles with semi-structured questionnaires and an activity in a non formal educational space, the Atlantic Forest Environmental Education Center (PEAMA) at Ifes/Alegre/ES. Content analysis was employed to interpret the collected data. Students demonstrated knowledge of environmental impacts common to both urban and rural areas, with water pollution, deforestation, and biodiversity loss being the most frequently mentioned impacts. After the intervention in the non-formal space, students expanded their understanding of the importance of environmental preservation, suggesting that activities in non-formal educational settings contribute to meaningful learning of concepts addressed in Biology, the focus of this study. The Biology curriculum content related to the theme of “environmental impact” and its consequences enhances students’ understanding and, thus, contributes to the formation of more critical and active citizens in the preservation of the environment.